PENGARUH PENERAPAN CERITA BERGAMBAR TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS II SD - Nisa'ul Ula, Rina Audria; Ni Luh Sakinah Nuraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning basic mathematics literacy in second-grade elementary schools often encounters challenges, especially in understanding word problems related to